Close relationships and self-regulation relationship satisfaction facilitates momentary goal pursuit. [article]. - Hofmann, Wilhelm; Finkel, Eli J.; Fitzsimons, Grainne M.
In the new millennium, scholars have built a robust intersection between close-relationships research and self-regulation research. However, virtually no work has investigated how the most basic and broad indicator of relationship quality, relationship satisfaction, affects self-regulation and vice versa. In the present research, we show that higher relationship satisfaction promotes a motivational mind-set that is conducive for effective self-regulation, and thus for goal progress and performance. In Study 1-a large-scale, intensive experience sampling project of 115 couples (total N = 230)-we closely tracked fluctuations in state relationship satisfaction (SRS) and 4 parameters of effective self-regulation according to our conceptual model. Dyadic process analyses showed that individuals experiencing higher SRS than they typically do exhibited higher levels of (a) perceived control, (b) goal focus, (c) perceived partner support, and (d) positive affect during goal pursuit than they typically exhibit. Together, these 4 self-regulation-relevant variables translated into higher rates of daily progress on specific, idiographic goals. In Study 2 (N = 195), we employed a novel experimental manipulation of SRS, replicating the link between SRS and parameters of effective self-regulation. Taken together, these findings suggest that momentary increases in relationship satisfaction may benefit everyday goal pursuit through a combination of cognitive and affective mechanisms, thus further integrating relationship research with social-cognitive research on goal pursuit. -- (from the authors)